Religion and digital culture: Changes in the worship orientation of Christians in Ambon - Paulus Koritelu; Lusanra. J. Tutkey (Digital Theory, Culture & Society, 2025)
The development of digital technology has had a significant impact on religious practices, including among Christians in the city of Ambon. This article discusses changes in the worship orientation of the Christian community in Ambon in the context of a rapidly developing digital culture. The presence of social media, worship streaming platforms, and digital Bible applications has shifted some of the traditional patterns of worship, which were previously centered on physical gatherings in churches, towards more flexible, personal, and virtual forms of worship. These changes not only affect personal spirituality, but also have social, cultural, and economic implications for church communities, such as the emergence of new relationship patterns, the redefinition of spiritual authority, and challenges in maintaining community unity. Using a qualitative approach through in-depth interviews, observation, and literature review, this article highlights how religion and digital culture interact in shaping the new face of Christianity in Ambon. Findings show that while digital culture expands religious access and experience, it also requires adaptive pastoral strategies to preserve the meaning of worship in this era of transformation.